The use of satellite beacon TEC data from GRBR campaign-based observations for ionosphere tomography over West Java Indonesia - Timbul Manik (Lembaga Penerbangan dan Antariksa Nasional, 2018)
The experiment of ionospheric tomographic reconstruction using satellite beacon TEC data from two or more adjacent GRBR observation stations following equatorial latitude and longitude have been conducted on campaign-based observation in Sumedang, Pameungpeuk and Indramayu West Java on 2016 and 2017. The reconstruction technique utilized is a simple algebraic reconstruction technique (ART). The result obtained is the ionosphere electron density distribution along the longitude of 108 degrees East over the area of West Java and Indonesia. The ionosphere electron density parameters obtained from the IRI-2012 Model were used as the initiation to construct ionospheric tomographic reconstruction. The validation performed by correlating foF2 from the ionospheric tomographic reconstruction with foF2 obtained from ionosonde observation at Sumedang station, one of the GRBR observation sites shows that corresponded to the correlation coefficient value of 0.8665, with a bias frequency of 1.386 MHz, whereas the correlation with the maximum electron density value obtained from the IRI-2016 model gives a correlation coefficient value of 0.8958. a bias frequency of 1.386 MHz, whereas the correlation with the maximum electron density value obtained from the IRI-2016 model gives a correlation coefficient value of 0.8958.